2020
DOI: 10.1016/j.jecp.2019.104788
|View full text |Cite
|
Sign up to set email alerts
|

Undersweep fixations during reading in adults and children

Abstract: Return-sweeps take a reader's fixation from the end of one line to the start of the next.Return-sweeps frequently undershoot their target and are followed by a corrective saccade towards the left margin. The pauses prior to correctives saccades are typically considered to be uninvolved in linguistic processing. However, recent findings indicate that these undersweep-fixations influence skilled adult reader's subsequent reading pass across the line and provide preview of line-initial words. This research examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 42 publications
3
15
0
3
Order By: Relevance
“…It is important to note that this prediction assumes that there is a leftward skew of attention when readers make return-sweeps (i.e., leftward saccades). This assumption is consistent with the notion that the movement of attention is consistent with the direction of the saccade that it precedes (Godijn & Pratt, 2002; Godijn & Theeuwes, 2003), and the observation that readers acquire information from the line-initial word when their line-initial fixation lands to its right (e.g., Parker et al, 2020). Of course, this is an open question as Veldre and Andrews (2014) reported that spelling ability did not influence the extraction of information to the left of rightwards moving intra-line fixations.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…It is important to note that this prediction assumes that there is a leftward skew of attention when readers make return-sweeps (i.e., leftward saccades). This assumption is consistent with the notion that the movement of attention is consistent with the direction of the saccade that it precedes (Godijn & Pratt, 2002; Godijn & Theeuwes, 2003), and the observation that readers acquire information from the line-initial word when their line-initial fixation lands to its right (e.g., Parker et al, 2020). Of course, this is an open question as Veldre and Andrews (2014) reported that spelling ability did not influence the extraction of information to the left of rightwards moving intra-line fixations.…”
supporting
confidence: 83%
“…Furthermore, there appears to be no such benefit for words to the right of an undersweep fixation, suggesting that the skew of attention is directed towards the start of the line following a return-sweep (c.f. Parker et al, 2020). One question that remains unanswered is the extent to which the distribution of attention changes during return-sweeps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate line-initial fixations are longer than intra-line fixations, likely because they land on text that has not been processed parafoveally (Heller, 1982 ; Parker et al, 2017 ). However, undersweep fixations are shorter than other reading fixations, as they are terminated quickly in order to move the eye to a better viewing location (Abrams & Zuber, 1972 ; Hofmeister et al, 1999 ; Parker et al, 2019a , b , 2020 ).…”
Section: Eye-movements During Oral Readingmentioning
confidence: 99%